Eficiência da tecnologia LED (Light-Emitting Diode) na captura de mosquito do gênero Anopheles (Diptera: culicidae) e vetores da malária - COSTA NETA, Benedita Maria (2017)
The use of LEDs was evaluated as attractants for insect vectors and there are several advantages over the standard incandescent lamp favoring the use of LED technology as alternative light source for sampling medically important mosquitoes. Therefore, other studies were conducted in order to evaluate the response to the different wavelengths; however data on the use of LEDs and light intensity to attract anopheline mosquitoes are scarce. This study main purpose was to evaluate the efficiency of LEDs and the influence of the light intensity in the captures of malaria vectors upon the lunar phases, in a peridomiciliary area in northeastern Maranhão, Brazil. In the first essay, incandescent lamps routinely used in CDC-type light traps were replaced for 5 mm LEDs (green – 520 nm; blue – 470 nm) to evaluate the response of anopheline mosquitoes to those alternative light sources. However, the incandescent lamp was used as control. To test the influence of moonlight, the collections were undertaken under the four lunar phases during the study period. In the second essay, it was analyzed the influence of light intensity on the captures of mosquitoes, six light traps with LEDs of different light intensities were used: green (10,000 mCD, 15,000 mCD and 20,000 mCD) and blue (4,000 mCD, 12,000 mCD and 15,000 mCD). As a result in the first essay, 1,845 specimens and eight species foi was sampled. The most frequent species were Anopheles evansae, accounting for 35.2%, followed by An. triannulatus s.l.(21,9%), An. goeldii (12,9%) and An. argyritarsis (11,5%). The green LED was the most efficient light source, it had attracted 43.3% of the individuals, followed by the blue LED (31.8%) and the control (24.9%). The LED traps were more attractive than the control, regardless the lunar phase. In all tests, the captures were more efficient when LEDs were used to attract the anopheline mosquitoes than when the control was used. As a result in the second essay, a total of 1,650 specimens and five species of anopheline mosquitoes were sampled. The blue LED attracted more individuals (953) than the green one (697). According to the light intensity, the green LED 20.000mCD had a greater attractiveness showing 39.2% increase related to the others intensities. While the blue LED 15.000mCD has attracted 50.2% of the specimens captured. The efficiency of LEDs improves light trapping results and it is suggested that the use of LEDs as an attractant for anopheline mosquitoes should be taken into consideration when monitoring mosquito populations. Thus, the light intensity was a very important factor in enhancing the light trap performance in attracting the mosquitoes; more intense the light, more insects attracted. However, the light intensity is an important attribute for sampling more efficiently insect vectors.